Web and Mobile-Based Sales System Using Rapid Application Development Method: Case Study : ALM Mart - Iqbal Satrio Nugroho; Farida Ardiani (Kirana Publisher (KNPub), 2026)
ALM Mart is a minimarket that still relies on manual transaction recording using cash books and calculators. Which often causes calculation errors, inaccurate stock data, and difficulties in generating sales reports. This research aims to develop an integrated sales system consisting of a web application for cashiers and administrators, as well as a mobile application for customers who want to order products online with a pickup at-store model. Development was carried out using the Rapid Application Development (RAD) method, which enables rapid prototyping and involves users at every stage. The system was successfully built within 8 weeks with complete features including digital cashier, automatic stock management, online ordering, Digital payment, and sales reporting. Black-box testing conducted with the store owner and customers showed that the system functions as expected and reduces transaction time by up to 60% compared to the previous manual method.